Mortality patterns of SLE and the associated risk factors in Korean patients: a nationwide cohort study - Sun-Young Jung; Yoon-Kyoung Sung; Soo-Kyung Cho; Eun Jin Jang; Yena Jeon; Jung-hyo Kim (Lupus Science and Medicine)
Background To evaluate the mortality patterns of SLE and the associated risk factors in Koreans.Methods Using the National Health Insurance database spanning 2008 to 2018, incident cases of SLE in patients aged 10–79 years were included. We analysed the all-cause mortality and cause-specific mortality, stratifying by sex and age. The mortality rate (MR) was calculated as the number of deaths per 100 000 person-years (PYs). The causes of death were identified by the International Classification of Diseases, 10th Revision codes during hospitalisation or emergency visit prior to death. A generalised estimating equation model was employed for risk factor analysis.Results In total, 11 375 incident SLE cases among patients with an average age of 42.3±16.7 years were recruited (86.1% female). During 57 658 PYs, 728 deaths occurred (MR 1262.62/100 000 PYs). The MR among men (2718.86/100 000 PYs) exceeded that among women (1060.57/100 000 PYs). The leading causes of death were SLE-related conditions (381.56/100 000 PYs), cardiovascular disease (CVD) (202.92/100 000 PYs), cancer (175.17/100 000 PYs) and infection (143.95/100 000 PYs). Of the SLE-related mortality, the key risk factors were pulmonary complications, such as pulmonary alveolar haemorrhage (OR 9.93), pulmonary arterial hypertension (OR 3.77) and interstitial lung disease (OR 3.27).Conclusions Among Korean patients with SLE, SLE-related conditions were the leading causes of mortality. However, CVD and cancer were also identified as the main causes of mortality. Furthermore, pulmonary manifestations were significantly associated with SLE-related mortality.